The Concepts, Applications, and Challenges of the Internet of Things - Siegfried, Patrick; Amangeldiyev, Nauryzbek (UIR PRESS, 2022)
The main aim of the study is to give the reader the basic meaning of an “Internet of Things” itself, evaluate its main concepts, types, trends, and areas of application, as well as challenges. The study is a basic and fresh literature review from general sources and researches on the topic that has been done recently by the scientific community. Qualitative and quantitative methods of data collecting have been used. As a result, this paper can offer new interpretations, theoretical approaches, or other ideas. Mendeley referencing application was used to cite and give credits to the authors of a raw material used in this study. This term paper will give an excellent understanding to other researchers who are trying to build basic concepts within the topic, or to those who wish to begin their researches on “IoT” furthermore and will provide effective and accumulation knowledge. Also, can be useful as a raw material to the introductory courses regarding “IoT”.